Cochrane Review Summaries—April 2020. Issue 4 (April 2020) - Kumar, Nimisha; Jahanfar, Shayesteh; Haas, David M.
Abstract : This feature highlights recently published Cochrane Reviews of interest to the readers of Obstetrics & Gynecology . This month, we focus on two obstetric reviews on umbilical cord clamping and induction of labor and one gynecology review on epithelial ovarian cancer. The brief summaries are published below and the complete references, along with a hyperlink, are listed in Box 1 Box 1. Abstracts Discussed in This Summary: Rabe H, Gyte GML, Díaz-Rossello JL, Duley L. Effect of timing of umbilical cord clamping and other strategies to influence placental transfusion at preterm birth on maternal and infant outcomes. The Cochrane Database of Systematic Reviews 2019, Issue 9. Art. No.: CD003248. Available at: https://doi.org/10.1002/14651858.CD003248.pub4 de Vaan MDT, ten Eikelder MLG, Jozwiak M, Palmer KR, Davies-Tuck M, Bloemenkamp KWM, et al. Mechanical methods for induction of labour. The Cochrane Database of Systematic Reviews 2019, Issue 10. Art. No.: CD001233. Available at: https://doi.org/10.1002/14651858.CD001233.pub3. Coleridge SL, Bryant A, Lyons TJ, Goodall RJ, Kehoe S, Morrison J. Chemotherapy versus surgery for initial treatment in advanced ovarian epithelial cancer. The Cochrane Database of Systematic Reviews 2019, Issue 10. Art. No.: CD005343. Available at: https://doi.org/10.1002/14651858.CD005343.pub4.